2020
DOI: 10.1111/sji.12964
|View full text |Cite
|
Sign up to set email alerts
|

The prospects of single‐cell analysis in autoimmunity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 160 publications
(276 reference statements)
0
3
0
Order By: Relevance
“…Goldstein and co-workers showed that single B cell sequencing can recover a higher number of antibody lineages compared to hybridoma technology ( Goldstein et al, 2019 ). Single-cell sequencing has also been used to identify SARS-CoV-2 specific Abs ( Woodruff et al, 2020 ; He et al, 2021 ), tumor-specific Abs ( Buus et al, 2021 ), and autoimmune disease-specific Abs ( Sulen et al, 2020 ; Jin et al, 2021 ). Single-cell sequencing is now readily available from several companies, including 10x Genomics and Takara Bio.…”
Section: B Cell Receptor Sequencingmentioning
confidence: 99%
“…Goldstein and co-workers showed that single B cell sequencing can recover a higher number of antibody lineages compared to hybridoma technology ( Goldstein et al, 2019 ). Single-cell sequencing has also been used to identify SARS-CoV-2 specific Abs ( Woodruff et al, 2020 ; He et al, 2021 ), tumor-specific Abs ( Buus et al, 2021 ), and autoimmune disease-specific Abs ( Sulen et al, 2020 ; Jin et al, 2021 ). Single-cell sequencing is now readily available from several companies, including 10x Genomics and Takara Bio.…”
Section: B Cell Receptor Sequencingmentioning
confidence: 99%
“…Single-cell measurements have revolutionized our ability to study the variation within and between heterogeneous cell populations 1,2 . As single-cell RNA-sequencing (scRNA-seq) and other high-dimensional single-cell techniques have become increasingly accessible, these technologies have extended to studies including multiple experimental conditions, samples, or subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Secondary lymphoid organs, such as spleen and lymph nodes, have also been in focus in animal studies. The knowledge that the immune system also included other sites in the body came much later, but now when techniques are available that make it possible to isolate and study small populations of the cells, such as single cell RNA sequencing, 6 the field of tissue immunology has taken off.…”
mentioning
confidence: 99%